2023
DOI: 10.3390/photonics10121306
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phase Information Propagation in the Realisation of Super-Resolution Based on Speckle Interferometry

Yasuhiko Arai

Abstract: Super-resolution technology is important not only in bio-related fields but also in nanotechnology, particularly in the semiconductor industry, where fine patterning is required and super-resolution is essential. However, observing microstructures beyond the diffraction limit proposed by Abbe and Rayleigh is considered impossible because of diffraction in traditional optical microscopy observation techniques. However, in recent years, it has been possible to observe microstructures beyond the Rayleigh criterio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…Consequently, the experimental results demonstrated that detecting the phase distribution according to the shape of the object was possible, even outside of the focal plane. Additionally, the validity of the simulation results presented in a previous paper [25] was experimentally confirmed. In the course of this verification process, it was also demonstrated that the spatial resolution of the present optical system could be easily improved by applying to it the traditional speckle-handling methods [26], commonly used in speckle interferometry.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…Consequently, the experimental results demonstrated that detecting the phase distribution according to the shape of the object was possible, even outside of the focal plane. Additionally, the validity of the simulation results presented in a previous paper [25] was experimentally confirmed. In the course of this verification process, it was also demonstrated that the spatial resolution of the present optical system could be easily improved by applying to it the traditional speckle-handling methods [26], commonly used in speckle interferometry.…”
Section: Introductionsupporting
confidence: 69%
“…Figure 6b,d show that a sinusoidal shape could be observed in almost the same manner, although the amplitudes were slightly different. These results show that the shape information of the object was preserved in the phase distribution of the reflected light from the object, not only considering the simulation results shown in [25], but also the experimental results.…”
Section: Investigation Of the Case Where The Objective Lens Was Out O...supporting
confidence: 63%
See 3 more Smart Citations